Electronic Word Of Mouth Music Studio - Fikri Zaka Rahmansyah; Satya Indra Karsa (UNISBA Press, 2022)
Abstract. People's habits as consumers always rely on reviews from other consumers before using products and services. Google Review is one of the platforms that is easily accessible and has credibility and is trusted to display various kinds of impressions, positive or negative criticism, and suggestions. The assessment on this google review is used by Rocket Music Studio 3 as a promotional medium in the form of electronic word of mouth. The purpose of this study was to understand the quality, quantity, and expertise of Rocket Music Studio 3's electronic word of mouth on google reviews and to find out the reasons for google reviews. The research method used is a qualitative research method with a content analysis approach. Data collection techniques are carried out by; interviews, observations, literature studies, documentation. The informant in this study is the owner of Rocket Music Studio 3. This research will result that the promotion of Rocket Music Studio 3 through electronic word of mouth on google reviews is based on the dimensions of Jeong & Jang's eWOM. This research results that the communication form of Rocket Music Studio 3's eWOM on Google Review is Online Customer Review and Online Customer Rating based on Jeonga & Jang's eWOM dimension. Abstrak. Kebiasaan masyarakat sebagai konsumen selalu mengandalkan review dari konsumen lain sebelum menggunakan produk dan jasa. Google Review menjadi salah satu platform yang mudah diakses serta memiliki kredibilitas dan terpercaya untuk menampilkan berbagai macam kesan, kritik positif atau negatif, serta saran. Penilaian pada google review ini dimanfaatkan oleh Rocket Music Studio 3 sebagai media promosi dalam bentuk electronic word of mouth. Tujuan penelitian ini untuk memahami kualitas, kuantitas, keahlian electronic word of mouth Rocket Music Studio 3 di google review dan mengetahui alasan google review. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan analisis isi. Teknik pengumpulan data dilakukan dengan cara; wawancara, observasi, studi pustaka, dokumentasi. Informan dalam penelitian ini adalah Owner dari Rocket Music Studio 3. Penelitian ini akan menghasilkan bahwa promosi Rocket Music Studio 3 melalui electronic word of mouth di google review berdasar pada dimensi eWOM Jeong & Jang. Penelitian ini menghasilkan bahwa bentuk komunikasi eWOM Rocket Music Studio 3 pada Google Review adalah Online Costumer Review dan Online Costumer Rating yang berlandaskan Dimensi eWOM Jeonga&Jang.